DEVELOPMENT OF LEARNING MATERIALS ON INDUSTRIAL CHEMISTRYLECTURE TO SUPPORT ECOPRENEURSHIP IN CHEMISTRY DEPARTMENT FMIPA UNESA - Novita, Dian; Tjahjani, Siti (JCER (Journal of Chemistry Education Research), 2017)
Learning materials have been developed which then conducted the study and validation to the expert lecturers and then tested to the students to find out the validity of the feasibility of learning materials in the field of Industrial Chemistry as one of the supporting subjects of Ecopreneurship in Chemistry Department. From the data obtained can be concluded that learning materials in the form of Lesson Plan, Worksheet, and Instrument Rating get very good criteria. These criteria are obtained based on theoretical feasibility and empirical feasibility. Based on these results, learning tools developed can be used as learning tools for Industrial Chemistry courses to support ecopreneurship.